Ekstrak Daun Beluntas (Pluchea indica Less.) sebagai Obat Antistres pada Ayam Broiler - D Setiaji; A Sudarman (Media Peternakan, 2005)
The aim of the study was to find a cheaper alternative antistress for broiler rather than the commercial synthetic one. Ninety DOC strain CP 707 were used in this study which were divided into 18 groups, each consist of 5 chicken and kept in the animal house with a litter system. This study used Completely Randomized Design with six treatments and three replications. The treatments were: 1) drinking water + commercial antistress as positive control, 2) drinking water without extract of beluntas leaf and without commercial antistress as negative control, 3) drinking water + 5% extract of beluntas leaf given continuously, 4) drinking water + 5% extract of beluntas leaf given discontinuously (given only at the time when commercial antistress was given), 5) drinking water + 10% extract of beluntas leaf given continuously, 6) water + 10% extract of beluntas leaf given discontinuously. The results showed that treatments significantly (P